Vanilla rivasii (orchidaceae), a new species from the colombian pacific region - Molineros Hurtado, Francisco; González Mina, Robert Tulio; Flanagan, Nicola S; Tupac Otero, J (Lankesteriana: International Journal on Orchidology, 2014)
We describe a new species of fragrant Vanilla from the Chocó biogeographic region of Western Colombia, named Vanilla rivasii sp. nov. in honor of the local farmer who drew it to our attention. This species is related to the Vanilla hostmannii group, also containing V. dressleri, V. ruiziana and V. cribbiana, with which it shares flower traits such as the showy, yellowish flower with thickened longitudinal venation in the lip apex. Vanilla rivasii is characterised by possessing: a long racemose inflorescence up to 60 cm in length, carrying up to 150 yellow flowers, with two to four open simultaneously; a trilobed labellum with a conspicuously bi-lobulated central lobe; and basally fused lateral sepals. Vanilla rivasii can be distinguished from the most morphologically-similar species, V. cribbiana and V. hostmannii, by the number of veins in the cushion-like structure of the lip and the larger size and higher number of flowers per inflorescence. This discovery highlights northern South America as a centre of diversity for this economically-important genus, and underlines the need for further botanical exploration in the highly biodiverse region of the Chocó.